Relationship between the polymorphism in the interleukin 1-β and the treatment time of patients subjected to a modified piezocision technique (Colombia Medica, 2020)
Aim:We aimed to evaluate the correlation between the polymorphism of the interleukin 1-Beta (IL1-β, +3954 C>T) and tooth movement, in a group of Colombian patients undergoing surgically accelerated orthodontic tooth movement.Methods:The study was nested to a controlled clinical trial. Blood samples were taken from 11 women and 29 healthy Colombian male volunteers between 18 and 40 years old, after 1 year of starting orthodontic treatment. The patients presented malocclusion class I, with grade II or III. To detect the genetic polymorphism of the nucleotide +3954 C to T in the IL-1β gene, we used a real-time PCR assay.Results:Eleven individuals presented the allele 2 (T) heterozygous with the allele 1 (T/C) and 19 individuals were homozygous for the allele 1 (C/C). When analyzing the presence of the SNP, no significant differences were found in any of the variables. The best treatment was reflected in Group 3 (selective upper and lower alveolar decortication and 3D collagen matrix) and Group 4 (only selective alveolar decortication in the upper arch, with 3D collagen matrix), with 27% and 35% more speed respectively than in the control group.Conclusions:Our analyses indicated that a reduction in the total treatment time can be mostly potentiated by using decortication and collagen matrices and not for the presence of the allele 2 in the IL-1β. Nevertheless, it is important that further studies investigate if the polymorphism could be associated with the speed of tooth movement and analyze the baseline protein levels.